PENGEMBANGAN BAHAN AJAR DIGITAL MATEMATIKA SMA KELAS X BERBASIS STEM - Cindy Anggraini Widodo; I Komang Sukendra; I Wayan Sumandya (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
STEM is an appropriate learning with the demands of the 21st century. This study aims to determine the steps for the development and quality of digital mathematics teaching materials for class X SMA based STEM on trigonometry material. The procedure uses the research and development adaptation Plomp development model that includes four stages, namely a preliminary investigation, design, realization/construction, and testing, evaluation and revision. Sources of data in this study are validators, mathematics teachers and students of SMA Negeri 7 Denpasar. The data collection technique used a validation questionnaire for validation tests, practicality questionnaires for practicality tests and tests for testing the effectiveness of teaching materials. The results of the initial validity test were declared